Learning Through Movies: How Lucky Baskhar Helps Understand Maslow’s Hierarchy of Needs - Bhattarai , Jay Raj (The Management Review, 2026)
This article examines Maslow’s Hierarchy of Needs through the lens of the 2024 Indian film Lucky Baskhar, released on October 31, 2024. Set in 1990s India, the film tells the story Baskhar, a bank cashier who struggles to meet his needs due to constant financial pressure. Helaterturns to fraud to get out of debt and humiliation. Maslow’s theory explains motivation through a hierarchy of five needs that appear in an ascending order: Physiological needs, safety, love and Belonging, Esteem, and Self-Actualization goals. Previous studies such as those on Life of Pi and The Danish Girl show how films illustrate survival, belonging, and self-acceptance. This research looks at Baskhar’s journey to understand the way people are motivated towards the fulfillment of higher order needs once the lower-level needs are satisfied. Unlike earlier studies, it explores how the Maslow’s ideas fit in non-Western cultures like India and Nepal, which share common values like duty to family. By examining Baskhar’s actions and dialogues, this study shows how movies can be utilized to make complex ideas comprehensible. It proves Lucky Baskhar helps students learn motivation in a way that fits Indian and Nepalese life.